Konsep Kecerdasan Intuisi Menurut Miftahul Luthfi Muhammad - Qonitatillah, Andrea (Jurnal Riset Agama, 2022)
This research has several objectives arranged on the basis of answering the problems that are the subject of discussion. Among them: 1) Concept of Intuitive Intelligence Perspective of Miftahul Lutfi Muhammad; 2) The Role of Sufism as a Means of Sharpening Intuitive Intelligence. This type of research is a subjective exploration by applying a literature study. He initiated the Triangle of Force theory as a form of implementing Sufism on its correlation to the concept of Intuition intelligence. The contents of the theory of "The Triangle of Force" version of Miftahul Luthfi Muhammad are 1) Indonesian Muslim people who behave mentally and behave to put God first (human mauhid); 2) Indonesian Muslim people who behave mentally and behave honestly (khuluqush-shidqi); 3) Indonesian Muslim people who behave mentally and behave sincerely (khuluqul-ikhlash).